Co-Combustion of Tire Pyrolysis Products and Wood Pellets - A. V. Grytsenko; N. V. Vnykova; O. I. Pozdnyakova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Thermal power plants remain one of the main sources of environmental pollution. The deterioration of the quality of traditional carbon-containing energy resources leads to the need to develop technologies for co-combustion of biofuel and coal at small and large power plants. The paper proposes the concept of using solid waste from tire recycling by adding to the composition of the mixed fuel “coal – wood waste” as a substitute for coal slag, which is formed during the utilization of worn-out tires by pyrolysis. The aim of the work was to determine the possibility of increasing the calorific value of wood pellets by co-firing with pyrolysis slag instead of coal without increasing the burden on the environment. At the same time, the following tasks have been set: to determine the lowest combustion heat of mixed fuels and assess its change when replacing coal with slag; to determine moisture content, total sulfur content, volatile matter yield, ash content of mixed fuels according to standard methods; to assess the change in these parameters when replacing coal with slag at the same component ratios; to determine the optimal ratios of components in mixed fuels, which will not increase the burden on the environment when replacing coal with pyrolysis slag. It has been determined that replacing coal with slag results in an increase in calorific value by 37–45 %, a decrease in ash content by 37–42 %, and an increase in the yield of volatile substances. At the same time, the sulfur content increases by 5.6–18 %. The use of traditional cleaning equipment is recommended in order to reduce the emission of sulfur dioxide. The research results make it possible to substantiate the possibility of replacing coal with slag in mixed fuels at certain ratios of components. A new direction of using solid products from recycling of rubber products, i.e. worn-out tires, has been proposed by the pyrolysis method in mixed fuels “slag-wood pellets” for small and medium-sized power plants.